2021
DOI: 10.1002/fsn3.2644
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fast food intake in Iranian households during the lockdown period caused by COVID‐19 virus emergency, National Food and Nutrition Surveillance

Abstract: Background Fast foods, though very popular, are commonly known as unhealthy foods. However, coronavirus pandemic may have influenced on food choices of the general population. This study investigated the changes in fast food consumption during epidemic lockdown 2020. Materials and Methods This study was part of a nationwide survey having been conducted using a web‐based electronic self‐administered questionnaire. The questionnaire link was extensively distributed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…They also reported that the consumption of fast foods, packaged frozen foods, and canned food had significantly decreased, while consumption of fruits, vegetables, meat, and healthy foods had moderately increased. Finally, Rabiei et al (2021) reported 74.8% reduction in fast food consumption among Iranian households.…”
Section: A Numerical Examplementioning
confidence: 99%
“…They also reported that the consumption of fast foods, packaged frozen foods, and canned food had significantly decreased, while consumption of fruits, vegetables, meat, and healthy foods had moderately increased. Finally, Rabiei et al (2021) reported 74.8% reduction in fast food consumption among Iranian households.…”
Section: A Numerical Examplementioning
confidence: 99%
“…This questionnaire consists of nine questions with four frequencies of occurrence (most of the time; sometimes; rarely; and never), which are scored on a Likert scale (lowest score = zero, highest score = 3). The total scores obtained from the questionnaire are divided into four categories: food secure (0-1), mild food insecure (2-7), moderate food insecure (8)(9)(10)(11)(12)(13)(14) and severe food insecure (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The validity and reliability of the Persian questionnaire has been previously assessed by Mohammadi et al (Cronbach's alpha = 0.85) (22).…”
Section: Household Food Security Assessmentmentioning
confidence: 99%
“…The purpose of the current study was to examine how food insecurity may be associated with fear of COVID-19 (a mental disorder which developed during the pandemic). Although studies have been conducted on the fear of COVID-19 in the areas of food packaging ( 19 ), fast food consumption ( 20 ), or food supply ( 21 ), but the fear of COVID-19 scale has not usually been used. Since mental health and food security have been severely damaged during the epidemic, examining their relationship can provide policymakers with evidence on how to adopt the strategies.…”
mentioning
confidence: 99%
“…Data about the questionnaire have been comprehensively presented previously [6,10]. Briefly, each respondent had to complete the questionnaire for his/her household.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Obviously, these changes can be different from one community to another [3]. Some of these changes might be toward healthy eating including adherence to Mediterranean diet, eating more fruits and vegetables [4,5] and decrease in fast foods and alcohol consumption [5,6]. On the other hand, in some communities unhealthy dietary changes such as increased consumption of high calorie snacks and alcohol have been reported [7].…”
Section: Introductionmentioning
confidence: 99%